Computed tomography features of traumatic pulmonary pseudocysts - Taydaş, Onur; Gümüş, Burak; Karavaş, Erdal (The European Research Journal, 2019)
Objectives: To discuss the radiological characteristics of traumatic pulmonary pseudocyst (TPP) detected by thorax computed tomography. Methods: Retrospective screening was made of 107 patients applied with thorax computed tomography due to blunt thoracic trauma between 2014 and 2017 at our hospital. Results: TPP was detected in 6 (5.6%) patients. The patients comprised 5 males and 1 female with a mean age of 28 years (range, 15-49 years). Blunt thorax trauma was caused by traffic accidents in 4 patients and a fall from height in 2 patients. Eleven (64.7%) of the lesions were located in the lower lobes. The most common finding associated with TPP was ground glass opacities, which were present in all of the patients and represented the parenchymal contusion. Conclusion: Thorax computed tomography is an effective and reliable method for early and definitive diagnosis of the rare development of TPP after blunt thoracic trauma.